Karakteristik Malformasi Anorektal di Rs. Bhayangkara dan RSIA Sitti Khadijah 1 Makassar Tahun 2017 – 2022 - Mega Islamiaty; M. Syakir; Rizal Basry; Aziz Beru Gani; Mahyuddin Rasyid (Universitas Muslim Indonesia, 2023)
Anorectal malformation (MAR) is considered as one of the most common congenital intestinal anomalies with an incidence of 1 in 4000 - 5000 births. The purpose of this study was to determine the characteristics of anorectal malformations at Bhayangkara Hospital & RSIA Sitti Khadijah 1 Makassar in 2017 – 2022. This research is a retrospective descriptive study with a cross sectional approach. This type of research was chosen because researchers wanted to find out about the characteristics of anorectal malformation cases at Bhayangkara Hospital & RSIA Sitti Khadijah 1 Makassar in 2018 – 2022. This study involved 13 samples. Based on research that has been done, that the majority of anorectal malformation patients at Bhayangkara Hospital and RSIA Sitti Khadijah 1 Makassar are male (69.2%), have a history of maternal ANC frequency of 4 times (46.2%), and do not have history of the mother taking drugs during pregnancy (61.5%). It was also found that the average birth weight was 2,661 ± 787 grams, the gestational age was 38 ± 1.5 weeks, and the mother's age at delivery was 30 ± 6.7 years. The incidence of anorectal malformations in Makassar is still low. From the data obtained from the two studies, it was not too significant between the two hospitals, Rs. Bhayangkara and RSIA Sitti Khadijah 1 Makassar.